Metode Consultant Social Science dalam Upaya Meningkatkan Kemampuan Kolaborasi dan Komunikasi Siswa - Kurniawati, Lestari (Jurnal Didaktika Pendidikan Dasar, 2020)
The purpose of the study was to improve students’ collaboration and communication skills using the Social Sciences Consultant method in class IX.D SMPN 1 Rangkasbitung. Research using quantitative descriptive methods, begins by conducting data collection, data analysis, making conclusions and description of data based on the conditions as they are. The results showed the Social Sciences Consultant’s method could improve aspects of Collaboration, sessions I and II, namely: 1). The Hasanudin group numbered 15% which was seen from the increase; 2). Imam Bonjol Group is 10% 3). Teuku Umar group is 5%; 4). Cut NyakDien’s group is 10%; 5). Kartini group is 5%; and 6). The Pattimura group is 20%. Communication Aspects 1). Hasanudin group is 10%; 2). Imam Bonjol’s group is 5%; 3). Teuku Umar group is 5%; 4). Cut NyakDien’s group is 10%; 5). Kartini group is 10%; and 6). Pattimura group is 10%.